1974
DOI: 10.1111/j.1749-6632.1974.tb26820.x
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Electrical Current on an Infecting Microorganism in Wounds*

Abstract: All health care personnel, especially those in the rehabilitation field, are quite familiar with the frustrations that ischemic skin ulcers engender, particularly decubiti. When preventive measures prove unsuccessful, one is faced with the problem of enhancing tissue repair of the resultant lesion. A satisfactory method for the treatment of these lesions has eluded physicians for centuries, and the variety of therapeutic techniques is exceeded only by the number of resistant ulcers.Ischemic ulcers are, by defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
53
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(54 citation statements)
references
References 4 publications
1
53
0
Order By: Relevance
“…This body of work has shown that electric fields and currents can be used for electroporation and electrofusion (31), electroosmosis, iontophoresis (6,(13)(14)(15), and the electroinsertion of specific proteins (30). During this work, it has been noted that electric fields and currents can influence the organization of biological membranes (10,28,31,35,40,42) and membrane analogs (1, 18), metabolic and developmental processes within both prokaryotic and eukaryotic cells (19,24,34,38,42) 994-1960. Fax: (406) 994-6098. kilovolt-per-centimeter range, but a significant number (5,13,15,24,36) have also focused on the effects of low-intensity fields and currents on biological systems for which significant effects have been documented, especially embryonic systems (34).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This body of work has shown that electric fields and currents can be used for electroporation and electrofusion (31), electroosmosis, iontophoresis (6,(13)(14)(15), and the electroinsertion of specific proteins (30). During this work, it has been noted that electric fields and currents can influence the organization of biological membranes (10,28,31,35,40,42) and membrane analogs (1, 18), metabolic and developmental processes within both prokaryotic and eukaryotic cells (19,24,34,38,42) 994-1960. Fax: (406) 994-6098. kilovolt-per-centimeter range, but a significant number (5,13,15,24,36) have also focused on the effects of low-intensity fields and currents on biological systems for which significant effects have been documented, especially embryonic systems (34).…”
mentioning
confidence: 99%
“…Consequently, device-related bacterial infections are aggressively treated with combinations of antibiotics (2, 27), but in many cases, the biofilm-colonized device must still be removed to facilitate the resolution of these infections (21,37). An increasing number of laboratories have begun to examine the effects of electric fields and current densities on biological systems (1,5,15,19,28,31,34,35,38,41), mainly because of interest in the electroporation and electrofusion processes that are very useful in genetic research (31). This body of work has shown that electric fields and currents can be used for electroporation and electrofusion (31), electroosmosis, iontophoresis (6,(13)(14)(15), and the electroinsertion of specific proteins (30).…”
mentioning
confidence: 99%
“…But most recent studies varied the type of treatment polarity during the healing process [9][10][11][12]. Rowley et al [13] and Barranco et al [14] showed that negative polarity has antibacterial effects. Kloth and McCulloch [1], Castillo et al [8], and Alvarez et al [15] suggested the use of positive polarity to augment the migration and proliferation of epithelial cells and therefore hasten wound closing.…”
Section: Introductionmentioning
confidence: 99%
“…Also, some useful effects of negative polarity include killing microorganisms [13][14], removing necrotic tissues due to decreasing pH of the wound environment [25], limiting protein molecule infiltration and therefore limiting formation of edema in the injury site [26], and increasing fibroblast cell proliferation and collagen synthesis [27][28].…”
Section: Introductionmentioning
confidence: 99%
“…There is a number of products known as capable of inhibiting microbial growth, including the conventional (orthodox medicine) antibiotics or antimicrobial agents (Mc Donnell and Rusell, 1999;Lavin, 2000;Takahashi et al, 2003) or by using unconventional approaches such as electric and magnetic fields; for instance, an early contribution from Rowley et al (1974), showed an inhibition of infecting microorganisms in human wounds by exposure to alternated electric fields. More recently, Qin et al (1996) reported that processing liquid foods with high-intensity pulsed electric fields, and inactivated micro-organisms.…”
Section: Introductionmentioning
confidence: 99%